Meal-feeding scheme: twenty years of research in Brazil - R.B. Bazotte; M.R. Batista; R. Curi (Brazilian Journal of Medical and Biological Research, 2000)
Naomi Shinomiya Hell was the first researcher to investigate the physiological adaptations to a meal-feeding scheme (MFS) in Brazil. Over a period of 20 years, from 1979 to 1999, Naomi's group determined the physiological and metabolic adaptations induced by this feeding scheme in rats. The group showed the persistence of such adaptations even when MFS is associated with moderate exercise training and the performance to a session of intense physical effort. The metabolic changes induced by the feeding training were discriminated from those caused by the effective fasting period. Naomi made an important contribution to the understanding of the MFS but a lot still has to be done. One crucial question still remains to be satisfactorily answered: what is the ideal control for the MFS?